Determinants of Purchase Decisions and Continued Use in Digital Ferry Ticketing Applications: An Extended Technology Acceptance Model Approach - Febrina Christina; Ricardo Indra (Al-Qalam Institute, 2025)
This study aims to examine the factors influencing user behavior toward the Ferizy application by applying an extended Technology Acceptance Model (TAM) integrated with a digital management communication perspective. The research employed a quantitative survey method with 266 active users, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that brand awareness and price value significantly and positively affect perceived ease of use, perceived enjoyment, and perceived quality. These perception constructs subsequently influence purchase decisions, which, in turn, drive continued use of the application. The results highlight that ease of use, enjoyment, and service quality are critical determinants of user decisions and of fostering long-term engagement with digital service platforms. Theoretically, this study contributes to TAM development by incorporating brand communication and price value as key external variables. In practice, the findings offer strategic insights for organizations to enhance digital communication, ensure transparent pricing, and improve service quality, thereby strengthening user satisfaction and sustained application usage.